2022
DOI: 10.1117/1.jbo.27.2.025001
|View full text |Cite
|
Sign up to set email alerts
|

Real-time tracking of a diffuse reflectance spectroscopy probe used to aid histological validation of margin assessment in upper gastrointestinal cancer resection surgery

Abstract: . Significance: Diffuse reflectance spectroscopy (DRS) allows discrimination of tissue type. Its application is limited by the inability to mark the scanned tissue and the lack of real-time measurements. Aim: This study aimed to develop a real-time tracking system to enable localization of a DRS probe to aid the classification of tumor and non-tumor tissue. Approach: A green-colored marker attached to the DRS probe was detected using hue-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The probe contained 6 peripheral illumination fibers together with a central light collection fiber, each measuring 600 micrometers in diameter, within a 0.125-inch ferrule in a cylindrical configuration. The instrumentation and setup have been previously described . A schematic representation and photograph of the instrumentation for data acquisition is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probe contained 6 peripheral illumination fibers together with a central light collection fiber, each measuring 600 micrometers in diameter, within a 0.125-inch ferrule in a cylindrical configuration. The instrumentation and setup have been previously described . A schematic representation and photograph of the instrumentation for data acquisition is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The DRS probe was connected to both the light source (HL-2000-HP; Ocean Optics) and the spectrometer (USB4000; Ocean Optics) to allow for data acquisition and sample illumination. All electronic devices communicated with proprietary software designed with Python version 3.6 (Python Software Foundation) on the laptop . VNIR indicates visible and near-infrared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning and empirical models, such as multivariate statistical algorithms, have also been used to distinguish between human tumors and surrounding tumor‐free tissues [10–12, 14, 21, 22, 32, 33, 37, 57–61]. The advantage is that no prior knowledge of the absorption and scattering properties of the tissue is required.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups are attempting to establish diagnostic criteria, or a form of "optical biopsy", based on the correlation between the histology and optical signatures of tissues, for a variety of human tissues, such as colon [9][10][11], skin [12][13][14], breast [15][16][17][18][19][20], cervical [21][22][23], oral [23][24][25][26][27], prostate [28][29][30][31], nasopharynx [32,33] and lung tissues [34][35][36][37]. Studies have also showed the potential of probe-based DRS to discriminate between human liver tumors and tumor-free surrounding tissue [7,8,[38][39][40][41][42][43].…”
mentioning
confidence: 99%